Changes in Drop-Jump Landing Biomechanics During Prolonged Intermittent Exercise. (March 2014) - Schmitz, Randy J.; Cone, John C.; Tritsch, Amanda J.; Pye, Michele L.; Montgomery, Melissa M.; Henson, Robert A.; Shultz, Sandra J.
Background: As injury rates rise in the later stages of sporting activities, a better understanding of lower extremity biomechanics in the later phases of gamelike situations may improve training and injury prevention programs. Hypothesis: Lower extremity biomechanics of a drop-jump task (extracted from a principal components analysis) would reveal factors associated with risk of anterior cruciate ligament injury during a 90-minute individualized intermittent exercise protocol (IEP) and for 1 hour following the IEP. Study Design: Controlled laboratory study. Level of Evidence: Level 4. Methods: Fifty-nine athletes (29 women, 30 men) completed 3 sessions. The first session assessed fitness for an IEP designed to simulate the demands of a soccer match. An experimental session assessed drop-jump biomechanics, after a dynamic warm-up, every 15 minutes during the 90-minute IEP, and for 1 hour following the IEP. A control session with no exercise assessed drop-jump performance at the same intervals. Results: Two biomechanical factors early in the first half (hip flexion at initial contact and hip loading; ankle loading and knee shear force) decreased at the end of the IEP and into the 60-minute recovery period, while a third factor (knee loading) decreased only during the recovery period ( P ≤ 0.05). Conclusion: The individualized sport-specific IEP may have more subtle effects on landing biomechanics when compared with short-term, exhaustive fatigue protocols. Clinical Relevance: Potentially injurious landing biomechanics may not occur until the later stages of soccer activity.